Analisis penggunaan aplikasi pembelajaran daring pendukung prestasi belajar siswa sekolah dasar di masa pandemi - Devina Kusuma Wardani; Sri Marmoah; Hadiyah Hadiyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This research to describe the use of applications that are used when online learning as a supporter of student achievement, learning processes and obstacles experienced. The method used is descriptive qualitative, case study approach. The research subjects were teachers and students of grades IV, V, and VI SD Angkasa Colomadu, collecting data through questionnaires, observations, interviews, and documentation. Validity technique with technique triangulation and source triangulation. The data obtained is then analyzed from three components, namely data reduction, data presentation, and drawing conclusions. The results of the study show that applications as learning resources and media are implemented in the learning process according to SE No. 15 of 2020, Ausubel's theory of meaningfulness, learning characteristics and principles, this makes evidence of learning achievement in Semester 1 PTS scores of the majority of students above the KKM and non-academic school activities.Applications commonly used are Whatsapp, Youtube, Google Meet and Zoom for communication and explaining material, as well as Google Classroom, Google Form and Quizizz used to work on evaluation questions. Barriers to application use are in the form of signals and quotas. It is concluded that the use of learning applications with the process is appropriate and supports learning.